37.2k views
5 votes
F(n)=3n-3
g(n)=n^2+4
find f(g(n))

User TylerTemp
by
5.3k points

2 Answers

4 votes

Answer: f(g(n)) = 3*n^2 + 9

Step-by-step explanation: This is function composition.

so

f (g(n) ) = 3 *( n^2 + 4) - 3

simplify:

f (g(n) ) = 3 *n^2 + 12 - 3 = 3*n^2 + 9

User Naamadheya
by
5.1k points
6 votes

Answer:

f(g(n)) = 3*n^2 + 9

Explanation:

This is function composition.

so

f (g(n) ) = 3 *( n^2 + 4) - 3

simplify:

f (g(n) ) = 3 *n^2 + 12 - 3 = 3*n^2 + 9

from the Great MysticChaCha :-)

User Chantale
by
4.5k points